Human–machine hybrid intelligence for the generation of car frontal forms. (January 2023) - Wu, Yu; Ma, Lisha; Yuan, Xiaofang; Li, Qingnan
Abstract: With the acceleration of the upgrading of the automobile consumption market, artificial intelligence has become an increasingly effective means of enhancing the creative design of automobile appearance modeling. However, when artificial intelligence processes specific design tasks, creativity is primarily based on data drive, resulting in machine-generated design schemes that do not match human-specific psychological intentions. Due to the absence of design knowledge in the process of machine design, there is a data gap between human cognitive thought and machine information processing. This paper aims to structure the human's complex cognitive knowledge of car frontal form, establish the consistency between human and machine cognitive structures, and reduce communication barriers in the process of human–machine hybrid creative design. To achieve this objective, a human–machine hybrid intelligence methodology – a combination of human cognitive mental model, human–machine shared knowledge base, and Generative Adversarial Networks (GAN) – was developed to generate a large number of car frontal forms that are consistent with the design intent. First, we constructed a mental model of human cognition based on three dimensions: design intent, drawing behavior, and functional structure. Second, we created a shared human–machine knowledge base with design Knowledge. This knowledge base contains 12, 560 images of car frontal form designs with corresponding morphological semantic labels and 3, 140 sketches of car frontal forms drawn by hand. Human–machine shared knowledge base data was utilized in a machine learning training network. In addition, a conditional cross-domain generative adversarial network was developed to investigate the implicit relationship between sketch characteristics, morphological semantics, and image visual effects. Using the suggested method, a large number of images with the specified morphological semantic category and resembling the hand-drawn sketch of a car frontal form can be generated rapidly. In terms of the quality of car frontal form generation, our research is superior to the baseline model according to qualitative and quantitative assessments. In comparison to the designer's output, the human–machine hybrid intelligent generation also demonstrates excellent creative performance.